2017
DOI: 10.14393/bj-v33n5a2017-36988
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the physiological response of pea plants (Pisum sativum L.) to iron deficiency (direct or lime- induced)

Abstract: Pea (Pisum sativum L.) is an important food crop in Tunisia, where calcareous soils represents the major limiting factor for agriculture production. In the present study a greenhouse experiment was conducted to assess the effects of direct and bicarbonate-induced iron deficiency on plant growth, chlorophyll fluorescence, photosynthesis, spad index and iron nutrition in two Tunisian pea genotypes (Pisum sativum L.). Plants were grown hydroponically and iron deficiency was induced for 3 weeks. Iron deficiency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
0
11
1
Order By: Relevance
“…Therefore, iron is considered as a necessary element for the most crops, in particularly legumes since it participates in atmospheric nitrogen fixation process. Moreover, iron has several important functions for plant growth and productivity, including photosynthesis and respiration processes and chlorophyll synthesis which they are functional tools for plant productivity and yield (Houimli et al, 2015;Ferhi et al, 2017;Mann et al, 2017 andRen et al, 2017). Since iron is impaired in alkaline soil due to the presence of CaCO 3, foliar-Fe fertilizer is highly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, iron is considered as a necessary element for the most crops, in particularly legumes since it participates in atmospheric nitrogen fixation process. Moreover, iron has several important functions for plant growth and productivity, including photosynthesis and respiration processes and chlorophyll synthesis which they are functional tools for plant productivity and yield (Houimli et al, 2015;Ferhi et al, 2017;Mann et al, 2017 andRen et al, 2017). Since iron is impaired in alkaline soil due to the presence of CaCO 3, foliar-Fe fertilizer is highly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Iron chlorosis is a yellowing of plant leaves caused by iron de ciency that affects many agricultural crops in the calcareous soils of Tunisia [1,2]. The primary symptom of iron de ciency is interveinal chlorosis, the development of a yellow leaf with a network of dark green veins.…”
Section: Introductionmentioning
confidence: 99%
“…These physicochemical conditions of soil affects the bioavailability of Fe and hamper plant growth and yield through the inhibition of Fe-dependent functions such as chlorophyll biosynthesis, photosynthesis, respiration, and protein formation [3]. Previous studies revealed the inhibitory effect of calcareousinduced iron chlorosis on several crops [1,2,4] and attributed the observed Fe de ciency not to the total Fe concentration in these soils but to the available fraction for the plant. Lindsay and Schwab [5] demonstrated that the very low solubility of iron oxides in calcareous soils is the result of the alkaline pH, buffered by the presence of bicarbonate ions.…”
Section: Introductionmentioning
confidence: 99%
“…Calcareous soils cover major cultivated land of south Mediterranean lands, which decreased crop growth and yield under low Fe availability. A lot of research showed that the most obvious effect of Fe deficiency is a decrease in the amount of chlorophyll pigments [ 7 , 8 ]. Therefore, there is a close relationship between plant growth and photosynthesis [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research showed that the most obvious effect of Fe deficiency is a decrease in the amount of chlorophyll pigments [ 7 , 8 ]. Therefore, there is a close relationship between plant growth and photosynthesis [ 7 , 9 ]. In fact, Mann [ 8 ] and Ren [ 9 ] showed that plants responded strongly to iron deficiency in physiological traits where chlorophyll content and plant biomass were reduced [ 10 ].…”
Section: Introductionmentioning
confidence: 99%